Fadiga por compaixão e seus desdobramentos nas UTIs de COVID-19, na perspectiva da teoria polivagal - Saito, Daniel Heiji (2024)
This investigation sheds light on the experiences of professionals, especially intensivist physicians, whoweresubjected to extreme exposure conditions in the workplace during critical phases of the covid-19 pandemic. Working in adult covid-19 ICUs, these professionals were exposed to a high risk of contagion. Long, exhausting work shifts with reduced rest periods, coupled with a fear of infecting close contacts, as well as the difficulties imposed by the shortage of work materials, constituted a landscape of mental health risk conducive to the onset of compassion fatigue. This syndrome is characterized by physical and emotional exhaustion stemming from the empathic cost of dealing with the suffering of others. Compassion fatigue has been a topic investigated only incipiently, which leads to the risk of its non-identification and consequent illness development, as it can be confused with stress or burnout syndrome. Compassion stress can, under extensive,intense conditions, lead to a state of compassion fatigue. Burnout consists of a response to chronic interpersonal stressors and presents three dimensions—namely, emotional exhaustion, depersonalization, and decreased personalaccomplishment—that distinguish it from the other states. The topic has relevance because dealing with the pandemic has been a major challenge of contemporary times. The purpose of this investigation was to study the emotional state, especially as regards compassion fatigue, of an intensivist physician who worked for at least six months in adult COVID-19 ICUs within the September 2020–June 2021 period. For better understanding of this state, the polyvagal theory was employed. Data for the present qualitative, exploratory, single-case study, conducted under analytical-descriptive orientation, were obtained by means of a prolonged interview. Content analysis uses assumptions for narrated material, with the identification of cores of meaning. Contributing to the study of quality of life and sustainable work among healthcare professionals is part of the commitment of the Pontifícia Universidade Católica de São Paulo to the goals of the 2030 Agenda of the United Nations. The objectives of this research align with Sustainable Development Goals 3 (“good health and well-being”) and 8 (“decent work and economic growth”) of the agenda. (Brazilian Council for Scientific and Technological Development – CNPq; grant 444582/2020-7.